Basic training for trainers : a handbook for new trainers - Kroehnert, Gary. (Sydney : McGraw-Hill, 2000)
This is a handbook for new trainers in basic training.
Keywords: Training; Employees; Organizations; Occupational training -- Handbooks, manuals, etc; Communication in organizations -- Handbooks, manuals, etc; Adult learning -- Handbooks, manuals, etc; Instructional systems -- Design; Employees -- Training of -- Handbooks, manuals, etc